DETERMINAN PARTISIPASI PRIA DALAM KELUARGA BERENCANA DI WILAYAH KERJA PUSKESMAS TENAYAN RAYA PEKANBARU TAHUN 2018: Determinan Partisipasi Pria Dalam Keluarga Berencana Di Wilayah Kerja Puskesmas Tenayan Raya Pekanbaru Tahun 2018 - sidri rizqi yuniati; Donel Suheimi; Nurhapipa Nurhapipa; Oktavia Dewi; Nurlisis Nurlisis (STIKes Hang Tuah Pekanbaru, 2019)
A family planning program is a program to help couples or someone to prevent unwanted pregnancies and reduce the incidence of high-risk pregnancies, morbidity, and mortality, create quality and affordable services, increase male participation and responsibility in family planning practices. The purpose of this study was to determine the determinants of male participation in family planning. Methods: This research is quantitative analytic using an observational method with a type of case-control design. This study was conducted in August-September 2018 in the working area of the inpatient health care center. The population of all men of childbearing age who are in the working area of the puskesmas is the large population of the case population of 712 people and the control population of 21,480 people.Research sample of 360 men couples of reproductive age divided into 2 groups, namely the case 180 group and the control group 180. purposive sampling sampling technique Data analysis was carried out in univariate, bivariate and multivariate. Results: This research is quantitative analytic using an observational method with a type of case-control design. This study was conducted in August-September 2018 in the working area of the inpatient health care center. The population of all men of childbearing age who are in the working area of the puskesmas is the large population of the case population of 712 people and the control population of 21,480 people.Research sample of 360 men couples of reproductive age divided into 2 groups, namely the case 180 group and the control group 180. purposive sampling technique Data analysis was carried out in univariate, bivariate and multivariate. Conclusion: Conclusion The dominant variable with male participation in family planning is the attitude variable. Suggestions Health workers are expected to do more counseling about male family planning, putting up posters, and leaflets about male family planning.